2011
DOI: 10.1016/j.cmet.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

PARP-2 Regulates SIRT1 Expression and Whole-Body Energy Expenditure

Abstract: Summary SIRT1 is a NAD+-dependent enzyme that affects metabolism by deacetylating key transcriptional regulators of energy expenditure. Here we tested whether deletion of PARP-2, an alternative NAD+ consuming enzyme, impacts on NAD+ bioavailability and SIRT1 activity. Our results indicate that PARP-2 deficiency increases SIRT1 activity in cultured myotubes. However, this increase was not due to changes in NAD+ levels, but to an increase in SIRT1 expression, as PARP-2 acts as a direct negative regulator of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
353
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 230 publications
(368 citation statements)
references
References 39 publications
11
353
4
Order By: Relevance
“…Recent reports revealed that the depletion of PARP-2 modifies the activity of multiple transcription factors [62][63][64]. In HepG2 cells depleted of PARP-2 by shRNA, we have found the dysregulation of more than 600 genes in microarray experiments (Szántó and Bai, unpublished data) indicating an important role for PARP-2 in the regulation of gene expression.…”
Section: Parp-2 In the Regulation Of Gene Expressionmentioning
confidence: 58%
See 4 more Smart Citations
“…Recent reports revealed that the depletion of PARP-2 modifies the activity of multiple transcription factors [62][63][64]. In HepG2 cells depleted of PARP-2 by shRNA, we have found the dysregulation of more than 600 genes in microarray experiments (Szántó and Bai, unpublished data) indicating an important role for PARP-2 in the regulation of gene expression.…”
Section: Parp-2 In the Regulation Of Gene Expressionmentioning
confidence: 58%
“…PARP-2 serves as a negative regulator of SIRT1 expression, as the absence of PARP-2 induces SIRT1 expression and results in higher SIRT1 activity [33,62]. PARP-2 binds to the murine SIRT1 promoter in a region between -1 --91, which is a highly conserved region among mammals, showing homology even in Xenopus [62].…”
Section: Interaction With Sirt1mentioning
confidence: 99%
See 3 more Smart Citations